Preparation and physical properties of chitosan scaffolds coated collagen from the skin of shark for bone tissue engineering - Jirut Meesane and Suttatip Kamolmatyakul, Kanokwan Srikhum (Naresuan University Journal: Science and Technology (NUJST); Vol 24 No 2 (2016): May-August 2016, 2016)
Secondary alveolar bone grafting is routinely practiced as the alveolar cleft treatment in cleft lip and cleft palate patient. Most commonly, bone for alveolar bone grafting is harvested from the iliac crests. As such, iliac crest harvesting procedures can result in paresthesia, hypersensitivity, infection and pelvic instability. In order to avoid these adverse effects, tissue engineering strategies may eliminate donor site morbidity by resorbable collagen sponge resulted in reduced donor site morbidity and decreased donor site pain intensity and frequency. The aim of this study was to investigate the effects of pepsin soluble collagen (PSC) from skin of brownbanded bamboo shark on the physical property of chitosan scaffolds. The collagen was characterized as type I collagen by Fourier transform infrared (FTIR) spectra and physical properties were studied in terms of morphology, water swelling and biodegradation of scaffolds. Physical property data were analyzed by Mann-Whitney U Test and using SPSS statistics version 16.0 program. The result of FTIR showed triple-helical structure of collagen type I. SEM demonstrated homogeneous microstructure and presence of interconnected micropores of both groups. Water swelling of PSC coated chitosan scaffolds was lower than chitosan scaffolds (p<0.001), whereas biodegradation tend to be lower (p>0.05). Biodegradation rates of both groups between different time points were statistically significant (p<0.05). In conclusion, PSC collagens improve physical properties of our novel chitosan scaffolds. (Supported by PSU grant # 950/427)   Keywords: Cleft lip and palate, Bone tissue engineering, Chitosan scaffold, Collagen
Keywords: Cleft lip and palate, Bone tissue engineering, Chitosan scaffold, Collagen